2015
DOI: 10.1002/jor.23133
|View full text |Cite
|
Sign up to set email alerts
|

Relative motion between the flexor digitorum superficialis tendon and paratenon in zone V increases with wrist flexion angle

Abstract: Carpal tunnel syndrome is characterized by non-inflammatory fibrosis of the subsynovial connective tissue (SSCT), a paratenon-like structure inside the carpal tunnel. This pathology suggests repetitive and/or excessive shear forces are involved in injury development. We assessed relative motion between the flexor digitorum superficialis (FDS) tendon and adjacent paratenon in Zone V using colour Doppler imaging as 16 healthy participants completed three long finger movements (metacarpophalangeal joint flexion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…When more finger joints are free to move, tendon displacement will increase. Thus, our maximum index tendon displacement of 27 ± 4 mm for an average 120°finger joint angle is a logical extrapolation from cadaver data (Kociolek and Keir, 2016;Lopes et al, 2011). Ring finger FDS tendon displacement has not been studied before.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…When more finger joints are free to move, tendon displacement will increase. Thus, our maximum index tendon displacement of 27 ± 4 mm for an average 120°finger joint angle is a logical extrapolation from cadaver data (Kociolek and Keir, 2016;Lopes et al, 2011). Ring finger FDS tendon displacement has not been studied before.…”
Section: Discussionmentioning
confidence: 59%
“…In various pathological conditions, the fingers and/or their tendons are affected, such as arthritis (Arauz et al, 2017), tenosynovitis and carpal tunnel syndrome (Bianchi et al, 2007;Kociolek and Keir, 2016;Korstanje et al, 2012;Singh et al, 2015;Tat et al, 2016). In patients with flexor tendon disorders, tendon displacements have been studied using ultrasound imaging (Korstanje et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, because the EDC tendon is very close to the surface of the hand, it can be visually identified, making it relatively easy to locate compared to other tendons in the human body. Third, previous studies have found that joint positions, movement velocity, and single-digit motion influence the extent of relative displacement between the tendon and its surrounding tissue 21 35 36 37 . However, the preceding variables were not included in the present study for the following reasons: For joint motion, the intrinsic-plus and intrinsic-minus position were considered a safer and more stable position for patients with metacarpal fracture.…”
Section: Discussionmentioning
confidence: 97%
“…The probe was positioned at the proximal wrist crease (Fig. A), in line with the area corresponding to zone V of the middle finger FDS tendon . The tendon was visually identified by its fibrillar‐striated pattern, which differs from the SSCT that appears as a thin hyperechoic band adjacent to the tendon (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, excessive shear strain (differential motion) between the flexor tendons and the adjacent SSCT can rupture parts of the collagen network, and has been suggested as a risk factor in the development and progression of CTS . Workplace risk factors such as repetitive motion, fast movement speeds, and flexed wrist postures have been shown to increase tendon‐SSCT shear strain during normal finger flexion‐extension, but the influence of mechanical compression and ischemia remains unknown.…”
mentioning
confidence: 99%